2016
DOI: 10.1126/sciadv.1501254
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic performance of Clostridium thermocellum explained by its wide range of cellulase modalities

Abstract: The multi–length scale nature of its glycoside hydrolase system explains the remarkable ability demonstrated by Clostridium thermocellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
93
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 46 publications
(68 reference statements)
0
93
0
1
Order By: Relevance
“…Interestingly, the regulation of Clo1313_1398 (man5A) in the two, similar C. thermocellum strains ATCC 27405 and DSM1313 appears to differ. Cthe_0821, the homolog of Clo1313_1398, was one of the most highly expressed genes when the cells were grown on biomass (7) and was in the top 6% of expressed genes grown on cellulose (5), while Clo1313_1398 was only in the top 30% of expressed genes when DSM1313 was grown on cellulose (2). The genomic architecture of this region does differ between the two strains, with DSM1313 lacking two transposase genes immediately upstream of Cthe_0821.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the regulation of Clo1313_1398 (man5A) in the two, similar C. thermocellum strains ATCC 27405 and DSM1313 appears to differ. Cthe_0821, the homolog of Clo1313_1398, was one of the most highly expressed genes when the cells were grown on biomass (7) and was in the top 6% of expressed genes grown on cellulose (5), while Clo1313_1398 was only in the top 30% of expressed genes when DSM1313 was grown on cellulose (2). The genomic architecture of this region does differ between the two strains, with DSM1313 lacking two transposase genes immediately upstream of Cthe_0821.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are bound to scaffoldins via type 1 cohesion-dockerin domain interactions, and this large complex is anchored to the cell wall by secondary scaffol-dins and type 2 cohesin-dockerin interations (1). In addition, the bacterium produces free enzymes and "cell-free" cellulosomes (2) and it is a candidate for cellulosic ethanol production (3). Wild-type C. thermocellum can utilize hexose sugars but not pentose sugars as fermentation substrates, despite having eight genes encoding xylanases (1).…”
mentioning
confidence: 99%
“…In fact, even those microorganisms that produce cell surface-anchored cellulosomes were found to produce free cellulosomes (14,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…CipA (primary scaffolding) has a significant role in cellulose degradation compared to other scaffoldings. Xu et al (2016) also reported that primary scaffolding (CipA) plays a key role in C. thermocellum for cellulose degradation.…”
Section: Cellulosementioning
confidence: 99%
“…Carbohydrateactive enzymes (CAZymes) play an important role in their activity and form large protein complexes (primary and secondary scaffoldings) that bond with the cell wall of bacteria. Xu et al (2016) studied the "cell-free" cellulosomal system and characterized two types of cellulosomal systems by using mutants with scaffolding gene deletions. CipA (primary scaffolding) has a significant role in cellulose degradation compared to other scaffoldings.…”
Section: Cellulosementioning
confidence: 99%